Fire management: A virtual treatment towards psychological preparedness among health college volunteers in Indonesia - Wijayanti, Dini Prastyo; Alfianto, Ahmad Guntur; Rahmawati, Ida; Yusniawati, Yustina Ni Putu (Palembang MediRose Publisher, 2023)
Background: Fire disasters in educational facilities often occur and lead to a lack of psychological readiness of volunteers in health colleges and in general. Objective: The study aimed to analyze the effects of fire management: A virtual short film on the psychological preparedness of university volunteers in Indonesia. Methods: This study uses quasi-experimental. The sampling technique used purposive sampling with a sample of 87 respondents who were divided into treatment and control groups. Health college volunteers were recruited from Java, Bali, and Sumatera islands. The psychological Preparedness for Disaster Threat Scale (PPDTS) questionnaire was used. The statistical test used is the paired t-test and the Independent Sample T-test. Results: We found a difference in volunteers’ psychological preparedness pre-treatment and post-treatment in the treatment group (p < 0.001) and control group (p = 0.800). Differences in both groups were significant (p < 0.001). Conclusions: Treatments using technology media, namely short films, can virtually influence increasing psychological preparedness for volunteers. In addition, this intervention can be used as media for health promotion that is easily accessible to everyone in the face of disasters.